Studi Perbandingan Hidrograf Satuan Sintetik pada Daerah Aliran Sungai Ciherang - Rahman, Fatchur; Nurudin, Fuad Ardian; Laksmi, Anasya Arsita (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
This study focuses on the hydrological analysis of the Ciherang Watershed using four Synthetic Unit Hydrograph (SUH) methods: Snyder-Alexeyev, Nakayasu, ITB-1, and ITB-2. Each method was applied to determine their effectiveness in predicting flood hydrographs based on the watershed's physical characteristics and rainfall data from 2013 to 2023. The results indicate that the Snyder-Alexeyev method produced a rise time of 4.43 hours, a recession time of 20.17 hours, and a peak discharge of 1.627 m³/s. The Nakayasu method, with the fastest rise time of 2.049 hours and a recession time of 20.49 hours, generated the highest peak discharge at 2.523 m³/s. The ITB-1 method showed a rise time of 2.951 hours, a recession time of 29.512 hours, and a peak discharge of 1.895 m³/s. The ITB-2 method resulted in a rise time of 2.049 hours, a recession time of 20.49 hours, and a peak discharge of 1.891 m³/s. Among the methods, Nakayasu and ITB-2 demonstrated the quickest response, with Nakayasu yielding the highest peak discharge. These findings provide essential insights for flood management and infrastructure planning in the Ciherang Watershed and similar regions.